2011
DOI: 10.3899/jrheum.110610
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Rituximab in Patients with Rheumatoid Arthritis: Observational Study from the British Society for Rheumatology Biologics Register

Abstract: ABSTRACT. Objective. To assess the effectiveness of rituximab (RTX) in patients with rheumatoid arthritis (RA) in routine clinical practice, and to identify predictors of 6-month response to RTX in patients for whom at least 1 anti-tumor necrosis factor-α (anti-TNF) therapy has failed. Method. The analysis involved 646 patients with RA registered with the British Society for Rheumatology Biologics Register (BSRBR) who were starting RTX and were followed for at least 6 months. Change in the 28-joint Disease Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
7
56
1
5
Order By: Relevance
“…An observational study from the BSRBR found no significant differences between RF-positive and RF-negative patients and response to rituximab. However, when the analysis was limited to those patients who had failed to respond to a previous anti-TNFα agent, a greater reduction in DAS28 was seen in RF-positive than RF-negative patients, although this did not correlate with a good/moderate EULAR response14 A summary of these studies is included in online supplementary table S2.…”
Section: Resultsmentioning
confidence: 99%
“…An observational study from the BSRBR found no significant differences between RF-positive and RF-negative patients and response to rituximab. However, when the analysis was limited to those patients who had failed to respond to a previous anti-TNFα agent, a greater reduction in DAS28 was seen in RF-positive than RF-negative patients, although this did not correlate with a good/moderate EULAR response14 A summary of these studies is included in online supplementary table S2.…”
Section: Resultsmentioning
confidence: 99%
“…BMI might be a predictive factor of IFX response in RA, but no study has evaluated the impact of BMI on rituximab (RTX) response in RA. Anti-CCP and RF positivity were found to be associated with better response to RTX [20][21][22]. Moreover, we recently published data of the same RA population suggesting that high anti-CCP titres could be associated with response to RTX [23].…”
Section: Introductionmentioning
confidence: 90%
“…In clinical practice, many patients initiating RTX have lower disease activity levels compared with those enrolled in anti-TNF RCT, a factor that further influences evaluations of effectiveness 12,13,14 . Most observational data examining the effectiveness of RTX in routine clinical practice have been reported from European registries 15,16,17,18,19,20,21,22 , with scant information currently available from the United States 23 . There is tremendous value in examining US cohorts of patients with RA to assess effectiveness because of the differences in treatment practices and patient characteristics.…”
Section: Rheumatologymentioning
confidence: 99%